Study on the Soft Magnetic Properties of FeSiB/EP Composites by Direct Ink Writing - Qing, Ma; Chong, Teng; Jing, Hu; Sun, Baoan (Frontiers in Materials, 2021)
Fe-based amorphous alloy has excellent soft magnetic properties, traditionally Fe-based amorphous alloy such as soft magnetic devices were fabricated by insulation enveloping and suppression molding methods. In these processing, the aging of organic envelope materials and the crystallization of Fe-based amorphous alloy were usually occurring, accompanying with low magnetic induction and poor mechanical properties. Direct ink writing technique can make complex-shaped parts and needs no heating treatment after forming, which can avoid the effect of traditional molding process. In the present study，varying mass fraction FeSiB/EP composites parts were prepared by direct ink writing technique with the Fe-based amorphous alloy powder and epoxy resin, which microscopic morphology, magnetic properties and mechanical properties of FeSiB/EP soft magnetic composites were studied . The results indicate that the slurry with iron powder mass fraction of 92.3wt%, 92.6wt% and 92.8wt% have good printing performance and self-support ability, which is suitable for direct ink writing. The density of the printed parts is about 4.317, 4.449, 4.537 g/cm3，which is almost similar with the iron powder. The tensile strength and elongation of printing parts are significantly improved compared with the pure epoxy resin. From the photos of microscopic morphology of printing parts, it can be seen that FeSiB powders are evenly dispersed in EP, no pores and defects, with the proportion increasing of powders, the insulation coating thickness decreases and the magnetic performance improves. The optimal sample is 92.8wt% FeSiB/EP, which saturation magnetic induction strength is 137.9759 emu/g, coercivity is 4.6523 A/m.